(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article talks about the importance of speech skills in assessing students’ professional potential, how to provide a good atmosphere in the course of the lesson, as well as how to improve the quality of education by increasing the effectiveness of the course.